Effect of Thermal Processing on the Structural and Magnetic Properties of Epitaxial Co2FeGe Films - Andrii Vovk; Dariia Popadiuk; Bogdan Postolnyi; Sergey Bunyaev; Pavel Štrichovanec; José Ángel Pardo; Pedro Antonio Algarabel; Olga Salyuk; Vladislav Korenivski; Gleb N. Kakazei; Vladimir O. Golub; João Pedro Araujo (Nanomaterials)
The structure and magnetic properties of epitaxial Heusler alloy films (Co2FeGe) deposited on MgO (100) substrates were investigated. Films of 60 nm thickness were prepared by magnetron co-sputtering at different substrate temperatures (TS), and those deposited at room temperature were later annealed at various temperatures (Ta). X-ray diffraction confirmed (001) [110] Co2FeGe || (001) [100] MgO epitaxial growth. A slight tetragonal distortion of the film cubic structure was found in all samples due to the tensile stress induced by the mismatch of the lattice parameters between Co2FeGe and the substrate. Improved quality of epitaxy and the formation of an atomically ordered L21 structure were observed for films processed at elevated temperatures. The values of magnetization increased with increasing TS and Ta. Ferromagnetic resonance (FMR) studies revealed 45° in-plane rotation of the easy anisotropy axis direction depending on the degree of the tetragonal distortion. The film annealed at Ta = 573 K possesses the minimal FMR linewidth and magnetic damping, while both these parameters increase for another TS and Ta. Overall, this study underscores the crucial role of thermal treatment in optimizing the magnetic properties of Co2FeGe films for potential spintronic and magnonic applications.